Perlawanan Ideologi Moderatisme Melawan Hegemoni Radikalisme Dalam Novel Tuhan, Izinkan Aku Menjadi Pelacur! Karya Muhidin M. Dahlan (Tinjauan Sosiologi Sastra: Hegemoni Gramsci) - Via Rahmawati (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
This research entitled "The Resistance of the Ideology of Moderatism Against Hegemony Radicalism In God's Novel, Allow Me to Become a Slut! The work of Muhidin M. Dahlan (Review of Sociology of Letters: Hegemoni Gramsci) ", focuses attention on the existence of two ideological oppositions in God's novel, Allow Me to Become a Whore! the work of Muhidin M. Dahlan. God's novel, Allow Me to Become a Whore! recounts religious organizations Jamaah Daulah Islamiyah who want to rule over the government of Indonesia and want to realize his ideals to establish Daulah Islamiyah Indonesia. The results of this study indicate that the ideology of moderateism that Kiran fought against the hegemony of radicalism Jamaah Daulah Islamiyah organization, although he must make strong resistance and protest against the organization.